Outcomes of Balloon Dilatation in Isolated vs. Risk-Associated Pulmonary Stenosis: A Comparative Study - Mumtaz, Saba; Sangi, Rumana; Ayyaz, Muhammad; Sher, Nazish Ali; Ahsan, Aliya Kemal; Kakar, Salahuddin; Korejo, Hussain Bux; Kumari, Veena; Shaikh, Abdul Sattar (Biological and Clinical Sciences Research Journal, 2025)
Pulmonary valve stenosis (PVS) is a common congenital heart defect, with balloon pulmonary valvuloplasty (BPV) being the standard intervention. However, outcomes can vary significantly between isolated cases and those associated with additional risk factors, such as dysplastic valves or right ventricular hypoplasia. Objective: T.o compare the outcomes of balloon dilatation in isolated versus risk-associated pulmonary stenosis (PS). Methodology: This cross-sectional study was conducted from January to December 2024 at the Pediatric Cardiology Department of NICVD, Karachi. Patients of any age and gender with echocardiographicaly confirmed pulmonary valve stenosis (PVS) undergoing balloon pulmonary valvuloplasty (BPV) were included. Isolated PS was defined as severe doming valves without additional risk factors; risk-associated PS included dysplastic valves, critical PS, multilevel obstruction, or RV/valvular hypoplasia. Pre- and post-procedural clinical, echocardiographic, and hemodynamic data were recorded. Follow-up echocardiography was performed on day one and at one month. Data were analyzed using IBM-SPSS Statistics. For all inferential statics, p<0.05 was considered statistically significant. Results: Of 61 patients, 36 (59%) had isolated, and 25 (41%) had risk-associated pulmonary stenosis. Risk-associated cases had lower median age (1.5 vs 7.0 years; p=0.015), smaller annulus diameter (8.0 vs 15.0 mm; p<0.001), and higher cyanosis (64.0% vs 19.4%; p<0.001). Day-1 RVSP was higher (74.0 vs 65.5 mmHg; p =0.016), and cardiac arrest occurred only in the risk group (16.0%; p=0.013). By day-30, restenosis occurred exclusively in risk-associated cases (21.1% vs 0%; p=0.010). At day-30, mortality occurred in 2 cases ( risk-associated PS). Conclusion: Balloon pulmonary valvuloplasty remains an effective therapeutic option for pulmonary stenosis. Patients with risk-associated features are more likely to experience higher residual RV pressures, greater regurgitant lesions, increased risk of cardiac arrest, and early restenosis.